2017
DOI: 10.1088/1361-6528/aa7356
|View full text |Cite
|
Sign up to set email alerts
|

Oriented epitaxial TiO2nanowires for water splitting

Abstract: Highly oriented epitaxial rutile titanium dioxide (TiO) nanowire arrays have been hydrothermally grown on polycrystalline TiO templates with their orientation dependent on the underlying TiO grain. Both the diameter and areal density of the nanowires were tuned by controlling the precursor concentration, and the template surface energy and roughness. Nanowire tip sharpness was influenced by precursor solubility and diffusivity. A new secondary ion mass spectrometer technique has been developed to install addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Because of the advantages of low cost, stable physical and chemical properties, and abundant material availability, wide-band-gap metal oxide semiconductors (SnO 2 , NiO, TiO 2 , CuO, ZnO, etc.) have been extensively applied in various fields, such as solar cells, lithium ion batteries, electro- or photo-catalysis, and gas sensors. The functionality of these semiconductor oxides is strongly dependent on the crystal structure especially the exposure of high energy surfaces, on which chemical reactions such as water splitting and gas dissociation can be easily realized. The exposed facets introduce more atom steps, edges, kinks, and dangling bonds, which usually have high chemical activity. , Hierarchical SnO 2 nanoflowers with high-index {113} and {102} facets exposed have shown high NO 2 gas sensing sensitivity and selectivity . Fe 3 O 4 with exposed {110} facets has shown a significant potential in lithium storage with good cycle performance and specific capability .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the advantages of low cost, stable physical and chemical properties, and abundant material availability, wide-band-gap metal oxide semiconductors (SnO 2 , NiO, TiO 2 , CuO, ZnO, etc.) have been extensively applied in various fields, such as solar cells, lithium ion batteries, electro- or photo-catalysis, and gas sensors. The functionality of these semiconductor oxides is strongly dependent on the crystal structure especially the exposure of high energy surfaces, on which chemical reactions such as water splitting and gas dissociation can be easily realized. The exposed facets introduce more atom steps, edges, kinks, and dangling bonds, which usually have high chemical activity. , Hierarchical SnO 2 nanoflowers with high-index {113} and {102} facets exposed have shown high NO 2 gas sensing sensitivity and selectivity . Fe 3 O 4 with exposed {110} facets has shown a significant potential in lithium storage with good cycle performance and specific capability .…”
Section: Introductionmentioning
confidence: 99%
“…The underlying grain structure of nanomaterials strongly affects their functional properties. Studies of well-defined semiconducting nanowires have identified specific effects of grain orientations, phase boundaries, and defect densities on electronic, optical, thermoelectric, and (photo)­electrochemical properties. A broader understanding of these phenomena across diverse semiconductor materials is crucial for the design of next-generation optical/electronic devices. Recent studies have also probed the effects of the grain structure on the catalytic properties of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%